Nachhaltige Exportwirtschaft durch Umweltstandards? Potenziale und Barrieren bei der Anpassung in der Kaffeeproduktion Costa Ricas - Mayer, Claudia (ERDKUNDE, 2003)
The last decade has seen a significant increase in attempts to integrate social and environmental aspects into the global coffee trade. Environmental standards guarantee the consumer environmentally friendly coffee production and the producer an increase in competitiveness by means of participation in a growing niche market. The article discusses several specific factors that to date prevent the implementation of organic standards from having a significant effect on a sustainable export economy. Positive and negative factors in the conversion to environmentally friendly coffee production can be found in the character of the standards themselves as well as in the interface of standards requirements with their natural, socio-economic and institutional contexts. Inadequate guidance in the reorientation towards environmentally friendly production persists in addition to a lack of economic incentives. Possible solutions in dealing with these obstacles, such as different forms of cooperation and complimentary state regulation, are introduced.